Use of palm oil clinker as drainage layer in green roof system - Anas Mohammed, Husian Kassim (2014)
Green roof has become widely used in most of modern countries in the world. It has many benefits in term of storm water management, urban heat island mitigation, and thermal performance which lead to energy conservation. The fact that Malaysia is being among one of the largest producer of palm oil in the world, Malaysia produces palm oil clinker as a waste materials as a by-product of extracting the oil. The palm oil clinker has the ability to replace the conventional material that had been used in the green roof system. This paper examines the usage of palm oil clinker to determine whether the palm oil clinker can replace the conventional materials (expanded clay, expanded shale, pumice, etc.). The ability for draining of palm oil clinker is studied since the purpose of drainage layer is to drain the excess water and to ensure aeration of substrate layer and roots. This study used an experimental procedure in which hydraulic conductivity, infiltration rate and bulk densities were measured. Besides, the experimental trays of selected green roof plants were also monitor to simulate the real green roof system. The results show that the palm oil clinker has a good ability of draining the excess water and there is no effect in term of plant development when the palm oil clinker is used as drainage layer.